“Breaking Even” under Intensification? Gendered Trade‐Offs for Women Milk Marketers in Kenya - Tavenner, Katie; Crane, Todd A.; Saxena, Tarangini (Wiley, 2021)
Despite the commonly vaunted “win‐win” prospect of combining intensified livestock production with greater gender equality, the benefits of formal marketization of livestock products are generally skewed toward men. In response to this global trend, there is a growing impetus to better understand the gender dynamics underlying women's market participation to curtail the risk of worsening gender inequalities in agricultural systems transitioning to intensified production. This study analyzes the spectrum of women's informal milk market practices in two Kenyan Counties undergoing dairy system intensification. Qualitative data were gathered from dairy stakeholders and market traders to explore the localized system of gender relations mediating women's engagement with milk markets and current practices. Results indicate that increased dairy intensification and informal market use is challenging existing gender norms and disrupting the boundaries between hegemonic (socially acceptable) and pariah (socially disruptive) gender relations. While women are generally better able to control the proceeds from their dairy labor in informal markets, they also face high social culpability and danger from engaging in illicit activities that transgress local norms. These contradictory “win‐lose” dynamics and trade‐offs highlight the contested nature of gender market relations under agricultural intensification and commercialization currently being pursued under low emissions dairy development (LEDD) in Kenya. The risk of exacerbating existing gender inequalities has profound implications for LEDD and agricultural intensification more broadly.